Implementation of augmented reality media through the metaverse approach in social science learning - Ade Budhi Salira; Dina Siti Logayah; Rizal Akbar Darmawan; Mina Holilah; Muhammad Arief Rakhman (Research and Development in Education (RaDEn), 2024)
The purpose of this study is to test and implement the feasibility of Augmented Reality (AR) media in social studies learning that has been designed in previous research, as well as develop an implementation strategy. Augmented Reality (AR) learning media focuses on teachers and students in the classroom in social studies learning. Meanwhile, AR media helps teachers contextualize social studies learning and can be used as a source of social studies learning Quantitative research approaches use research designs and methods, namely through product testing or socialization, the level of effectiveness using pseudo-experiments in three schools in Bandung City Junior High School. The study results provide information about the feasibility and testing of AR media products that are suitable for use in social studies learning. This states that 97% of students are interested in AR learning. The effectiveness of AR media applications in social studies learning obtained a very high response from students, 90%, while the responses of teachers and students showed promising results in using AR media applications in the classroom.